(untitled) (Tạp chí Y học Cộng đồng, 2022)
Objective: To analyze the adherence to treatment with Lamivudin, Tenofovir, Dolutegravir in HIV patients at Long An General Hospital. Subjects and methods: Study of cross-sectional description, no intervention through retrospective medical records and interviews with questionnaires on 71 HIV/ AIDS patients being treated with a 3-drug ARV regime of Lamivudin, Tenofovir, Dolutegravir including inpatient and outpatient treatment at the Department of Infectious Diseases, Long An General Hospital. Results: The rate of adherence to ARV of study participants within 7 days before the time of interview was 63.4%. In which, 11.3% of patients missed at least one dose of the drug; 22.5% of patients took the medicine at the wrong time over 1 hour at least once; 5.6% of patients took ARV drugs incorrectly at least once. The study results showed that the relevant factors for ARV adherence were the patient’s age, the clinical stage before treatment and the home reminder method. Conclusion: The rate of adherence to treatment of ARV in study participants within 7 days before the time of interview was 63.4%. Relevant factors for adherence to treatment of ARV were patient age, pre-treatment clinical stage, and home reminders.